2011
DOI: 10.1039/c0mb00244e
|View full text |Cite
|
Sign up to set email alerts
|

Identifying selective inhibitors against the human cytosolic sialidase NEU2 by substrate specificity studies

Abstract: Aberrant expression of human sialidases has been shown to associate with various pathological conditions. Despite the effort in sialidase inhibitor design, less attention has been paid to designing specific inhibitors against human sialidases and characterizing the substrate specificity of different sialidases regarding diverse terminal sialic acid forms and sialyl linkages. This is mainly due to the lack of sialoside probes and efficient screening methods, as well as limited access to human sialidases. Low ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
102
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 57 publications
(115 citation statements)
references
References 63 publications
8
102
0
Order By: Relevance
“…Arthrobacter ureafaciens sialidase, Vibrio cholerae sialidase, and Clostridium perfringens sialidase (CpNanH) were purchased from Prozyme (Hayward, CA, USA). Recombinant PmAldolase [19], NmCSS [20, 21], PmST1 M144D mutant [23], Pd2,6ST [24], Psp2,6ST A366G mutant [26], hNEU2 [28], PmST1 [22], SpNanA [30], SpNanB [30], SpNanC [32], and BiNanH2 [29], were expressed as described previously. Neu5Acα2–3Galβ p NP ( 17 ), Neu5Acα2–6Galβ p NP ( 18 ), Neu5,9Ac 2 α2–3Galβ p NP ( 19 ), Neu5,9Ac 2 α2–6Galβ p NP ( 20 ) [15], and ManNAc6NAc [11] were synthesized as reported previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthrobacter ureafaciens sialidase, Vibrio cholerae sialidase, and Clostridium perfringens sialidase (CpNanH) were purchased from Prozyme (Hayward, CA, USA). Recombinant PmAldolase [19], NmCSS [20, 21], PmST1 M144D mutant [23], Pd2,6ST [24], Psp2,6ST A366G mutant [26], hNEU2 [28], PmST1 [22], SpNanA [30], SpNanB [30], SpNanC [32], and BiNanH2 [29], were expressed as described previously. Neu5Acα2–3Galβ p NP ( 17 ), Neu5Acα2–6Galβ p NP ( 18 ), Neu5,9Ac 2 α2–3Galβ p NP ( 19 ), Neu5,9Ac 2 α2–6Galβ p NP ( 20 ) [15], and ManNAc6NAc [11] were synthesized as reported previously.…”
Section: Methodsmentioning
confidence: 99%
“…Sialidases used include six recombinant sialidases and three commercially available sialidases. The recombinant sialidases used were human cytosolic sialidase hNEU2 [28], bacterial sialidases PmST1 (a multifunctional sialyltransferase which also has sialidase activity) [22], Bifidobacterium infantis sialidase NanH2 [29], and three Streptococcus pneumoniae sialidases SpNanA [30], SpNanB [30], and SpNanC [31, 32]. Three commercial bacterial sialidases used were those from Arthrobacter ureafaciens, Vibrio cholerae , and Clostridium perfringens .…”
mentioning
confidence: 99%
“…Only NEU2 has been crystallized to date (58), although the other related sialidases have been homology-modeled to this structure (59). Unlike bacterial sialidases, human NEU2 has been demonstrated to have very similar activity on Neu5Ac and Neu5Gc in ␣2-3 or ␣2-6 linkage to an underlying galactose residue (60). To our knowledge, there are no reports examining the cleavage of ␣2-8-linked Neu5Gc by vertebrate exosialidases.…”
mentioning
confidence: 99%
“…14 We have also shown that replacing the C9-OH group of Neu5Ac in sialosides by a fluorine atom, a hydrogen atom (deoxy-Neu5Ac), or an azido group does not significantly change the activities of all bacterial sialidases tested although human NEU2 is quite sensitive to C9-modifications on Neu5Ac 11 Here we show that both Streptococcus pneumoniae sialidase (Figure 3D) and Clostridium perfringens sialidase (Figure 3E) as well as human NEU2 (Figure 3F) are quite sensitive to Neu5Ac C7-fluorine substitution which diminishes their activities significantly. Azido-substitution at C7-OH of Neu5Ac is also not well tolerated by either human NEU2 or bacterial sialidases tested except for the α2–6-sialidase activity of Clostridium perfringens sialidase which remains a reasonable activity (50%) compared to non-modified Neu5Acα2–6Galβ p NP substrate (Figure 3E).…”
Section: Resultsmentioning
confidence: 99%
“…911,13 Selective sialidase inhibitors against human NEU2 or bacterial sialidases have been designed and synthesized based on the structural features of the sialic acid modification obtained from sialidase substrate specificity studies. 14,15 Nevertheless, the method has not been used for the synthesis of sialosides containing C7-modified sialic acids.…”
Section: Introductionmentioning
confidence: 99%